Socialization of the human trafficking crimes protection in Sajingan Besar District, Sambas Regency - Hardi Alunaza; Sri Haryaningsih; Arifin Arifin; Ira Patriani; Antonia Sasap Abao (Universitas Muhammadiyah Magelang, 2022)
The border region of Sambas has the potential to become a point of entry and exit for human trafficking. The reason for this is that there are more job applicants than the job vacancies. The purpose of this service program is to provide education to the public regarding the causes and prevention of the crime of human trafficking against women and children in Sajingan Besar District. This activity is in the form of socialization and education to the public using three sub-discussions, namely the causes of the crime of human trafficking, forms, and protection. The results of this program indicate that there are changes before and after the program. The target community is better informed about the types of human trafficking and the care and protection they require. The implication of this program is also to make people in Sajingan Besar District more careful with the potential for human trafficking crimes in border areas.